Temporal Course of the Tourette Syndrome Clinical Triad. (26th September 2014) - Shprecher, David R.; Rubenstein, Lindsay A.; Gannon, Keenan; Frank, Samuel A.; Kurlan, Roger
Background: Tourette syndrome (TS) is a disorder characterized by childhood onset of motor and phonic tics, often with improvement of tic symptoms by young adult years. The temporal course of tics and commonly comorbid behavioral symptoms is still not well characterized. Methods: In order to clarify the time course of tics and comorbid attention deficit hyperactivity disorder (ADHD) or obsessive compulsive disorder (OCD) in TS, we administered a brief survey regarding the course of symptoms at a single point in time to 53 TS patients aged 13–31 years. Results: Mean age (±SD) at symptom onset was 7.9 (±3.6) years for tics, 7.9 (±3.5) for ADHD, and 9.2 (±5.0) for OCD. Age at peak symptom severity was 12.3 (±4.6) years for tics, 10.8 (±3.8) for ADHD, and 12.6 (±5.5) for OCD. Tics, ADHD, and OCD were reported to be no longer present in 32.0%, 22.8%, and 21.0% of subjects, respectively. Decline in symptom severity began at age 14.7 (±3.7) years for tics, 13.9 (±2.9) for ADHD, and 15.1 (±5.0) for OCD. Remission of symptoms occurred at age 17.4 (±3.8) years for tics, 17.4 (±1.3) for ADHD, and 15.6 (±2.3) for OCD. Discussion: Our data confirm and expand previously reported TS spectrum symptom milestones and may guide design of future research aimed at improving the course of TS.